Lactoferrin-osteopontin complexes: insights into intestinal organoid bioavailability and gut microbiota modulation - Camilla Ceroni; Loïc Dayon; Pieter Van den Abbeele; Aline Roch; Juliane Dervaux; Marion Ernest; Pascaline Sirugue; Aurélien Baudot; Marine R.-C. Kraus; Nathalie Brandenberg; Jonathan O’Regan; David Goulding; et al. (Communications Biology)
Abstract Lactoferrin (LF) and osteopontin (OPN) are key bioactive milk proteins with significant immune-modulatory, gut, and systemic health benefits. We investigated the bioavailability and intestinal uptake dynamics of bovine LF-OPN soluble complexes (SC) and complex coacervates (CC) using a microarrayed high-throughput 3D apical-out intestinal organoid platform, which closely mimics the human intestinal epithelium. Our findings revealed that both SC and CC complexes exhibited cellular uptake compared to individual LF and OPN components. Nevertheless, complexation did not compromise intestinal organoid viability, even following extended exposure. Further, an ex vivo bioreactor-based colon fermentation study using infant fecal microbiota demonstrated that LF-OPN complexes significantly influenced microbial metabolic activities. This modulation leads to enhanced production of short-chain fatty acids (SCFAs), particularly elevating butyrate levels, a key metabolite for sustaining gut health. The phylogenetic analysis highlighted significant shifts in microbial composition, favoring beneficial bacterial families such as Bacteroides fragilis, Phocaeicola dorei, Parabacteroides spp., and Clostridium symbiosum for complex bioactives. Our findings indicate that LF-OPN complexes have significant potential to further optimize infant nutrition by enhancing the bioavailability of bioactive compounds and promoting gut health through microbiota modulation.